Facility for Transformation of Magnetic Characteristics of Weak Magnetic Oxidized Iron Ores in Order to Improve Technologies for Iron Ore Concentrate Production - Ponomarenko, O.M.; Brik, A.B.; Dudchenko, N.O. (Science and Innovation, 2024)
New facility for continuous recording of iron ore magnetization intensity depending on temperature, when heating iron ores in the presence of reducing agent has been designed. The facility enables recording the transformation of weak magnetic minerals into strong magnetic ones under the influence of reducing agents and temperature, as well as determining the Curie temperature of the minerals. Using the facility it has been showed that heating of goethite and hematite in the presence of 4 % starch within the temperature range of 300–600 °С leads to a significant increase in the sample magnetization intensity. X-ray diffraction has confirmed that under the mentioned conditions the structure of hematite and goethite transforms into the magnetite structure. Obtained results open up new possibilities for the development of effective technologies for oxidized iron ore beneficiation.